Activated Hepatic Stellate Cells Promote the M1 to M2 Macrophage Transformation and Liver Fibrosis by Elevating the Histone Acetylation Level. (12th September 2022) - Chen, Junru; Huang, Xueqing; Huang, Zhi; Cao, Yu
Abstract : Liver fibrosis results from the formation of fibrous scars of hepatic stellate cells by various chronic liver diseases. Considering that the liver is the most important metabolic organ in the human body, exploring the metabolic characteristics of liver fibrosis is expected to discover new markers and therapeutic targets. In this study, we first used mouse model to verify that both lactate content and histone acetylation levels were significantly increased in hepatic fibrosis mice. At the same time, it was confirmed that activated hepatic stellate cells (HSCs) cocultured with M1 macrophages can promote their transformation into M2 macrophages in hepatic stellate cell line and primary hepatic stellate cells. In addition, the addition of lactic acid to the medium in which M1 cells are cultured can promote their transformation into M2 macrophages. Therefore, we concluded that activated HSCs can promote the transformation of M1 to M2 macrophages through lactate accumulation, thereby causing liver fibrosis.